Teaching writing with wiki-based collaborative writing tasks in an EFL context at higher education - Zennure (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2023)
This study explored university students’ attitudes towards wiki-based collaborative writing tasks and their perceptions of the effects of these tasks on their writing development in an EFL (English as a Foreign Language) context in Turkey. A total of 40 university students participated in wiki-based collaborative writing tasks. Wiki-based collaborative writing tasks enabled students to collaborate with their peers wherever or whenever they wanted, negotiate with each other, give and receive feedback, and take responsibility during the process of writing. Qualitative and quantitative data were collected during this 5-week intervention. This included two questionnaires and semi-structured interviews. Descriptive analysis and qualitative content analysis were used to analyse the data. The results indicate that the students considered wiki-based writing activities motivating, innovative and effective in their writing development in English. The research findings are discussed in terms of their implications for foreign language writing.